PENGEMBANGAN SEKTOR EKONOMI KREATIF MELALUI STRATEGI BRANDING BANDUNG CREATIVE CITY FORUM (BCCF) DALAM MENGHADAPI TANTANGAN MASYARAKAT EKONOMI ASEAN (MEA) - Iwan Koswara; Firman Alamsyah Taufik Robbi (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Bandung included in the creative world city network UNESCO (United Nations Educational, Scientific and Cultural Organization) or the UNESCO Creative Cities Network (UCCN) along with 47 other cities from 33 countries. This achievement is inseparable from the role of Bandung Creative City Forum (BCCF) as a cross-community forums and creative organization declared and established by a variety of creative community in the city. Bandung Creative City Forum (BCCF) or the Society for Creative Communities Bandung is a cross-community forums and creative organization declared and established by a variety of creative community in the city on December 21, 2008. In support of the development of the creative sector, BCCF form a networking media named CEN (creative entrepreneur Network) which is one of the branding strategy in marketing creative products produced by creative entrepreneurs Bandung. The CEN existence was to accommodate the various types of creative entrepreneurial community located in the city of Bandung. CEN where the latter can become a center of creative networking among economic operators, to provide events to network, build skills and knowledge for local entrepreneurs through workshops, seminars, business clinics, and so on. Branding strategy run by BCCF is Brand Recognition, Brand Preference, Brand insistence, and Lovely Brand / Brand Satisfy able to stimulate the stakeholders both inside and outside the country to participate and make Bandung as a creative city, where it can really help entrepreneurs Bandung to continue to hone their creativity in creating a variety of products that can compete in the global market. Therefore, BCCF role in developing the community spirit of Bandung to continue participating in the scope of the creative economy becomes necessary to remember that the map of global economic competition, especially in ASEAN more competitive thanks to the program of the ASEAN Economic Community (AEC).